Micellization behavior of cationic and anionic surfactant mixtures at different temperatures: Effect of sodium carbonate and sodium phosphate salts. (5th May 2019) - Mahbub, Shamim; Rub, Malik Abdul; Hoque, Md. Anamul; Khan, Mohammed Abdullah; Kumar, Dileep
Abstract: Herein, we applied the conductivity measurement technique in order to estimate the critical micelle concentration ( cmc ) of pure sodium dodecyl sulfate (SDS) and cetyltrimethylammonium bromide (CTAB) as well as their mixed systems in attendance of different salts at five various temperatures. The micellization of SDS + CTAB mixed systems was found to take place at intermediate cmc values of the two pure surfactants. The values of cmc dwindle with the enhancement of the mole fraction of CTAB. The cmc values follow different trend in different salts. The degree of the interaction between SDS and CTAB in occurrence of salt was estimated from the experimentally estimated value of cmc and their ideal values ( cmc id ). The observed cmc of individual surfactants along with their mixed systems dwindles in the occurrence of the electrolyte. The values of micellar mole fraction, X 1, of CTAB at different stoichiometric mole fractions of CTAB was determined on the basis of different proposed models mentioned in the literature. Different thermodynamics parameters were estimated from the magnitudes of the degree of counterion dissociation and cmc at different temperatures. The magnitudes of free energy of micellization ( ∆ G m o ), interaction parameter ( β ), and excess free energy (∆ G ex ) estimated for the studied systems were obtained to be negative in absence/attendance of electrolyte at all temperatures. The values of activity coefficients ( f 1 and f 2 ) were also determined on the basis of different proposed models. All of the estimated results signify the strong interaction between the studied amphiphiles. Abstract : Herein, we applied the conductivity measurement to estimate the critical micelle concentration ( cmc ) of pure SDS and CTAB as well as their mixed systems in attendance of different salts at various temperatures. Different thermodynamics parameters were estimated and discussed in detail. The magnitudes of free energy of micellization ( ∆ G m o ), interaction parameter ( β ) and excess free energy (Δ G ex ) estimated for the studied system were obtained to be negative. All evaluated results signify the strong interaction between the components.